Identification And Mapping Of Potential Processing Industry Types With Location Quotient (LQ) In Boyolali District - OKTAVIANI, SILFINA DWI; Muhammad, Katon; Krisnawati, Maria (Journal of Industrial and Mechanical Engineering, 2024)
In the current era of regional autonomy, regional economic development should be conducted sustainably across all fields, sectors, and sub-sectors in a programmed manner. Sustainable regional economic development is influenced by comparative advantages, regional specialization, and the economic potential of a particular area. The primary objective of regional economic development is to enhance the well-being of the community through an increase in the quantity and variety of job opportunities. Empowering Small and Medium Enterprises (SMEs) is one way to boost employment opportunities, involving a significant workforce and identifying competitive sectors in the region to enhance regional economic development. Boyolali Regency has shown relatively good growth in SMEs; however, there is a lack of mapping for basic sectors within these SMEs. This absence may lead to suboptimal utilization of available labor and production outcomes. Therefore, this research aims to identify and map SMEs with the potential to absorb more labor in Boyolali Regency. The Location Quotient (LQ) method is utilized to identify basic and non-basic types of SMEs using labor data from SMEs in Boyolali Regency. LQ calculations demonstrate that each SME has various basic sectors. This analysis produces mapping data of basic SMEs that can be used as a reference for more targeted development in SMEs, leading to increased job absorption.